2017
DOI: 10.1007/s11695-017-2634-5
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Liver Transplantation and Sleeve Gastrectomy: Prohibitive Combination or a Necessity?

Abstract: Previously, many morbidly obese (MO) patients were denied liver transplantation (LT) because of the higher operative risk. However, nowadays, 5 and 10 years graft survival is the rule, and patients whose lives can be prolonged with LT are dying of obesity-related comorbidities. Recent experience suggests that weight reduction in MO liver transplant recipients would improve their long-term survival. The bariatric surgery before LT is contraindicated for patients with decompensated cirrhosis, while post-transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…Our study showed a longer median operative time in LT+ patients in comparison to LT only (451 vs. 355 min, p = 0.002). Previous studies showed a slightly longer, albeit statistically insignificant, median operative time in patients undergoing an additional splenectomy or sleeve gastrectomy at time of LT by 34-48 min [12,14,25,26]. The statistically significant difference in operative time between our LT+ and LT only patients is likely a reflection of the greater range and complexity of additional operations included in the study (e.g., colectomies, coronary artery bypass graft, cardiac valve replacements, and Whipple procedure).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Our study showed a longer median operative time in LT+ patients in comparison to LT only (451 vs. 355 min, p = 0.002). Previous studies showed a slightly longer, albeit statistically insignificant, median operative time in patients undergoing an additional splenectomy or sleeve gastrectomy at time of LT by 34-48 min [12,14,25,26]. The statistically significant difference in operative time between our LT+ and LT only patients is likely a reflection of the greater range and complexity of additional operations included in the study (e.g., colectomies, coronary artery bypass graft, cardiac valve replacements, and Whipple procedure).…”
Section: Discussionmentioning
confidence: 55%
“…The outcomes of patients receiving an additional operation at the same time as LT have not been extensively studied, with the majority of current literature limited to small case series focusing on specific operations only [12][13][14][15][16][17][18][19]. This study aims to compare patients who underwent an additional operation at the same time as their LT to patients who underwent LT alone in terms of donor and recipient characteristics as well as short-term and long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Only 1 patient had a complication related to the bariatric surgery procedure, a leak at the gastric staple line. Since this initial report, a few more small case series have been published with similar findings[ 116 , 117 ]. Zamora-Valdes et al[ 118 ] recently updated the long-term results from the initial study, reporting that patients who underwent combined transplantation and sleeve gastrectomy maintained weight loss and had a lower incidence of diabetes, hypertension, and hepatic steatosis at 3 years after LT than did those who had pre-LT weight loss without bariatric surgery.…”
Section: Pre-transplant Considerations For Patients With Nashmentioning
confidence: 60%
“…The Mayo Clinic has performed the largest series of liver transplantation immediately followed by sleeve gastrectomy and have obtained excellent long‐term results . A recent series from Israel confirmed the feasibility of performing a combined liver transplant and sleeve gastrectomy . Many of these patients had a significant amount of weight loss that was largely maintained in the long‐term.…”
Section: Discussionmentioning
confidence: 99%